The Motives of Managers, Environmental Restraints, and the Theory of Managerial Enterprise - Baldwin, William L. (Quarterly Journal of Economics, 1964)
I. Introduction, 238. — II. Behavioral assumptions underlying theories of managerial enterprise, 239. — III. Target rate of return pricing as a managerial tool, 244. — IV. Management goals and restraints on managerial autonomy, 248. — V. Implications for the theory of the firm, 253.